THE RELATIONSHIP BETWEEN PHILOSOPHY AND EDUCATION - Khabib Choiriyah; Feni Handayani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Among the many branches of Islamic religion, philosophy is a science. The critical study of all phenomena of human life and intellect expressed in basic concepts is known as philosophy. Studying philosophy involves stating problems accurately, seeking answers, and offering appropriate justifications and arguments for a particular solution rather than conducting tests and experiments. It is impossible to separate philosophy from its various fields, including the philosophy of education. One of the fields of philosophy that examines the nature of teaching and its implementation is called the philosophy of education. Among the topics discussed are the goals, history, techniques, outcomes, and character of education. Its approach is a critical analysis of the benefits and structures of education. Among the specific criticisms is the interaction between teachers and students during the educational process. In terms of ontology, epistemology, or axiology, educational activities are considered as objects of study in the philosophy of education